Experimental study on concrete by partial replacement of cement with fly ash and coarse aggregates with palm kernel shells (Pks) and with addition of hybrid fibers - Siva Shanmukha Anjaneya Babu Padavala; Subhashish Dey; G.T.N. Veerendra; Akula Venkata Phani Manoj (Chemistry of Inorganic Materials, 2024)
Now a day’s production of sustainable concrete is a significant issue because of the reduction in raw sources. Thus, the present investigation attempts to investigate the strength characteristics of lightweight concrete produced by substituting the cement with Fly Ash (FA) and Palm Kernel Shells (PKS) with Coarse Aggregate (CA). In this investigation grade of concrete, M30 was considered. In the first phase, cement is partially replaced with FA indifferent proportions like 5, 10, 15, 20, 25 and 30 ​%, respectively. In the second phase, by keeping the optimum FA content constant, the CA is partially replaced with PKS in different proportions, i.e. 5 ​%, 10 ​% and 15 ​%. In addition to that, the effect of hybrid fibers is also studied. The results showed that the concrete produced by replacing 25 ​% of cement with FA and 10 ​% of CA by PKS along with 1.2 ​% fibers gives optimum strength. This suggests that lightweight concrete with low-cost can be produced by combining FA and PKS, thus delivering reasonable housing and conserving raw resources.